Comparative Nephroprotective Effects of Extracts of Buchholzia coriacea on some Biochemical Parameters in Carbon Tetrachloride-induced Toxicity in Rattus novergicus - Ugwu, Godwin C.; Okanya, Chinagorom L.; Egbuji, Jude V.; Okwo, Jude I.; Nnamonu, Emmanuel I.; Eyo, Joseph E. (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Buchholzia coriacea (wonderful kola) is a medicinal plant that has been used worldwide as an alternative medication to promote human health. Comparative nephroprotective effects of crude seed powder, aqueous and methanolic extracts of B. coriacea in hepatotoxic rats was investigated for 56 days. The crude powder (BCCP), aqueous extract (BCAE) and methanolic extract (BCME) significantly reduced (p<0.05) the levels of creatinine and uric acid and decreased minimally throughout the treatment periods. Total protein increased significantly (p<0.05). Significant decrease (p<0.05) were observed with 200 mg/kg BCAE and BCCP respectively in urea and BUN levels. Noticeable nephroprotective effects may be attributed to the presence of phytochemicals like flavonoids and tannins which act as antioxidants. This study has demonstrated that B. coriacea crude seed powder, methanolic and aqueous extracts caused no adverse effect on the rat kidney and may be recommended for the management of nephrotoxicity Dhaka Univ. J. Pharm. Sci. 17(2): 227-235, 2018 (December)